Evidence against mood-congruent attentional bias in Major Depressive Disorder. Issue 2 (15th December 2015) - Cheng, Philip; Preston, Stephanie D.; Jonides, John; Mohr, Alicia Hofelich; Thummala, Kirti; Casement, Melynda; Hsing, Courtney; Deldin, Patricia J.
Abstract: Depression is consistently associated with biased retrieval and interpretation of affective stimuli, but evidence for depressive bias in earlier cognitive processing, such as attention, is mixed. In five separate experiments, individuals with depression (three experiments with clinically diagnosed major depression, two experiments with dysphoria measured via the Beck Depression Inventory) completed three tasks designed to elicit depressive biases in attention, including selective attention, attentional switching, and attentional inhibition. Selective attention was measured using a modified emotional Stroop task, while attentional switching and inhibition was examined via an emotional task-switching paradigm and an emotional counter task. Results across five different experiments indicate that individuals with depression perform comparably with healthy controls, providing corroboration that depression is not characterized by biases in attentional processes. Highlights: Attention bias in depression examined across five experiments (3 tasks). Selective attention, attention switching, and attention inhibition tested. No mood-congruent attention bias detected in depression across five experiments.